Coalition formation for unpopular reform in the presence of private reputation costs - Evguenia Winschel (University of Mannheim, Department of Economics, 2012)
This paper studies coalition formation under asymmetric information. An outside party offers private payments in order to influence the collective decision over an unpopular reform. The willingness to accept such payments is private information. The paper demonstrates that a supermajority coalition induces truth-telling and secures the implementation of the decision for a price close to the full information minimal winning coalition price. On the contrary, if the minimal winning coalition is formed, then no revelation is possible.
urn:nbn:de:bsz:180-madoc-330061
Keywords: D71; D72; 330; coalition formation; minimal winning coalition; supermajority coalition; private information